The Relation between Price and Marginal Cost in U.S. Industry - Hall, Robert E. (Journal of Political Economy, 1988)
An examination of data on output and labor input reveals that some U.S. industries have marginal cost well below price. The conclusion rests on the finding that cyclical variations in labor input are small compared with variations in output. In booms, firms produce substantially more output and sell it for a price that exceeds the costs of the added inputs. The paper documents the disparity between price and marginal cost, where marginal cost is estimated from annual variations in cost. It considers a variety of explanations of the findings that are consistent with competition, but none is found to be completely plausible.